Analysis of Interactive Media Needs Based on Scratch in the Subject “Traditions and Culture of Society” for Fourth Grade Students in Kragan District - Nikmah Layarani; Nur Fajrie; Fina Fakhriyah (Institut Studi Islam Muhammadiyah Pacitan, 2025)
This study aims to analyze the needs of interactive media based on Scratch for teaching the